2015
DOI: 10.1108/bij-02-2013-0019
|View full text |Cite
|
Sign up to set email alerts
|

A performance evaluation framework for technical institutions in one of the states of India

Abstract: Purpose – Technical education plays an important role in the development of a country in this age of knowledge economy. Indian technical education system is facing many opportunities and challenges, one of which is how to assess the performance of technical institutions based on multiple criteria. The purpose of this paper is to describe and illustrate an application of a structured approach to determine relative efficiency and ranking of a set of private engineering colleges under multi-criter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Das et al (2015) maintain the association of Quality of Research output and teaching. The Quality of Research, which is measured as the number of publication in journals (reflecting international repute and indices such as SCOPUS, SCI, SSCI, etc.…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…Das et al (2015) maintain the association of Quality of Research output and teaching. The Quality of Research, which is measured as the number of publication in journals (reflecting international repute and indices such as SCOPUS, SCI, SSCI, etc.…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…MOOSRA (multiobjective optimization based on simple ratio analysis) was developed by Das et al (2012) to overcome the problems found in other MCDM techniques. Das et al (2015) used MOOSRA for evaluating performance in the education system. They initially formed the…”
Section: Moosra Methodsmentioning
confidence: 99%
“…Evaluation of the performance of engineering educational institutes is a difficult task because of their intangible nature (I-Huei et al , 2001; Das et al , 2015). But the performance can be compared in terms of their relative efficiencies (Tasopoulou and Tsiotras, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%